ANALISIS HUKUM PRIVATISASI BADAN USAHA MILIK NEGARA DALAM PRESPEKTIF PASAL 33 AYAT (4) UUD 1945 - Isdian Anggraeny (Legality : Jurnal Ilmiah Hukum, 2016)
The constitutional mandate of Article 33 Constitution - the welfare of the people and the community needs to establish the state-owned does not seem to be carried to the maximum so bergulirlah privatization policy. Strengthening this policy led to the privatization provisions in Act Number 19 of 2003 about Corporate Government . In connection with the birth of the concept of privatization which is the concept of capitalism, the author felt the need to analyze the law on the privatization of state-owned enterprises in Indonesia in the perspective of Constitution Article 33 paragraph (4). This study shows that the policy direction expected Privatization is a system of management of state enterprises more efficient and productive and achieve good corporate governance principles. To achieve that goal setting is certainly Corporate Government privatization in the Act should remain in line with the spirit of the economic constitution contained in Constitution Article 33 paragraph (4) because the state continues to run control function through the sectors regulation privatized state enterprises carry out its activities.